The Influence of Workload And Occupational Health Safety (K3) On The Performance of Employees of Pt Hokkan Deltapack Industri - Ayu Handayani; R. Padil; H. Mustaqim (International Journal of Business and Quality Research, 2023)
This study aims to determine the effect of workload and occupational health safety (K3) on the performance of employees of PT Hokkan Deltapack Industri Branch. The sample in this study were 64 employees of PT Hokkan Deltapack Industri Branch Kampar. Sampling using census technique. Data collection techniques in this study were interviews and questionnaires with data analysis using descriptive methods and using multiple regression. The conclusion obtained is that partially workload has a significant effect on employee performance at PT Hokkan Deltapack Industri Branch Kampar. Partially, occupational health safety has a significant effect on employee performance at PT Hokkan Deltapack Industries, Kampar Branch. Simultaneously workload and occupational health safety have a significant effect on employee performance at PT Hokkan Deltapack Industries Kampar Branch. For this reason, the authors suggest that employees or companies should improve and see the need for facilities and tools that employees need to work so that work can be carried out quickly and properly. Companies should pay more attention, especially to the health and safety of employees at work, by providing guarantees for occupational health and safety, it will make employees feel cared for and cared for by the company. Employee performance should be further enhanced by improving and managing workload and occupational health and safety for employees. For future researchers, so that research can be carried out in other companies or agencies, by redeveloping variables and indicators that have not been used in this study, such as motivation, work skills, attitudes and work ethics so that it is hoped that they will get a good company goal.